2022
DOI: 10.18632/aging.203848
|View full text |Cite
|
Sign up to set email alerts
|

The effect of QiangGuYin on osteoporosis through the AKT/mTOR/autophagy signaling pathway mediated by CKIP-1

Abstract: Osteoporosis is a systemic bone disease characterized by decreased bone mass and deterioration of bone microstructure, which leads to increased bone fragility and increased risk of fractures. Casein kinase 2 interacting protein 1 (CKIP-1, also known as PLEKHO1) is involved in the biological process of bone formation, differentiation and apoptosis, and is a negative regulator of bone formation. QiangGuYin (QGY) is a famous TCM formula that has been widely used in China for the clinical treatment of postmenopaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous clinical studies have shown that QGY is highly effective in treating PMOP ( Shi, Liu, and Li, 2007 ; Shi et al, 2008 , 2017 ; Xiao et al, 2019 ; Li et al, 2021 ; Mao et al, 2021 ; Hui et al, 2022 ). Studies have also shown that QGY promotes bone formation and inhibits bone resorption ( Wu et al, 2008 ; Wang, Wu, and Shi, 2016 ; Yao et al, 2016 ; Liu et al, 2018 ; Yang et al, 2018 ; Huang, Shi, and Deng, 2019 ; Liang et al, 2019 ; Yuan et al, 2022 ). Thus, we studied the effects of SBT, QGY, SBT + QGY, and SBT + EU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have shown that QGY is highly effective in treating PMOP ( Shi, Liu, and Li, 2007 ; Shi et al, 2008 , 2017 ; Xiao et al, 2019 ; Li et al, 2021 ; Mao et al, 2021 ; Hui et al, 2022 ). Studies have also shown that QGY promotes bone formation and inhibits bone resorption ( Wu et al, 2008 ; Wang, Wu, and Shi, 2016 ; Yao et al, 2016 ; Liu et al, 2018 ; Yang et al, 2018 ; Huang, Shi, and Deng, 2019 ; Liang et al, 2019 ; Yuan et al, 2022 ). Thus, we studied the effects of SBT, QGY, SBT + QGY, and SBT + EU.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that CKIP-1 regulates bone metabolism ( Liu et al, 2018 ; Yang et al, 2018 ) and that QGY acts as an anti-osteoporosis agent by inhibiting CKIP-1 and Akt binding in osteoblasts, activating the Akt/mTOR signaling pathway, inhibiting cellular autophagy, promoting osteogenic differentiation, and promoting osteoporosis ( Yuan et al, 2022 ). QGY also influences osteoblast differentiation through the Wnt/β-catenin pathway by affecting the expression of related miRNAs in the exostome of osteoclasts ( Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a systemic bone disease characterized by deterioration of the bone microstructure and decreased bone mass, which leads to increased risk of fractures and bone fragility 78 . An omnigenic model or effect is widely thought to be a reasonable way to explain and understand such complex diseases 23 , 24 , as such a model posits that small changes in hundreds or even thousands of genes can lead to a large outcome (i.e., disease).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK/mTOR signaling pathway is also a classical signaling pathway of autophagy, which not only indirectly regulates the functions of osteoblasts and osteoclasts, but also directly participates in the formation of osteoblast mineralization and osteoclast frill ( 28 ). A study has shown that activation of AKT/mTOR signaling pathway can inhibit autophagy, promote cell differentiation, and ultimately play an anti-osteoporosis role ( 29 ). AMPK is also a recognized autophagy regulator that promotes autophagy by inhibiting phosphorylation activation of its downstream target of rapamycin receptors ( 30 ).…”
Section: Discussionmentioning
confidence: 99%